When Celebrity CEOs Undermine Sustainability Value: Evidence from Indonesian Firms - Dwi Nova Wijaya; Wendy Wendy; Helma Malini (Journal of Economics, Business, and Accountancy Ventura, 2024)
This research investigates the moderating effect of celebrity CEOs on the relationship between corporate sustainability and firm value. A quantitative approach was utilized, analyzing data from 51 companies listed on the Indonesia Stock Exchange from 2014 to 2021 using regression analysis. While prior studies have explored the individual effects of either celebrity CEOs or corporate sustainability on firm value, this study addresses a gap by examining the interaction between these factors and its impact on firm value. The results reveal that although both the presence of a celebrity CEO and the implementation of corporate sustainability initiatives can enhance firm value, they do not necessarily create a beneficial synergy. In fact, the presence of a celebrity CEO may diminish the positive effects of corporate sustainability on firm value. These findings provide empirical evidence suggesting that companies should carefully assess the alignment between a CEO’s characteristics and the firm’s sustainability strategies to optimize value creation. The study underscores the importance of selecting a CEO whose attributes align with the company’s long-term sustainability objectives. These insights have practical implications for corporate management in making strategic decisions regarding CEO appointments and the execution of sustainability initiatives.